2005
DOI: 10.4103/0253-7613.13856
|View full text |Cite
|
Sign up to set email alerts
|

Self-medication among urban population of Jammu city

Abstract: (Wardha) for allowing us to do biochemical investigations in the biochemistry department. We also extend our sincere thanks to the staff for their full cooperation and technical assistance. The authors also wish to acknowledge the central drug store, M.G.I.M.S, Sevagram for providing chemicals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
62
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 3 publications
6
62
2
Order By: Relevance
“…12 Some studies show prevalence as high as 50-70%. [7][8][9]13,15,17 Previous studies have shown that self-medication is more common with the educated and affluent. 7,12 The fact that our study population mainly belonged to lower socio economic class, could be responsible for lower rate of selfmedication in our subjects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 Some studies show prevalence as high as 50-70%. [7][8][9]13,15,17 Previous studies have shown that self-medication is more common with the educated and affluent. 7,12 The fact that our study population mainly belonged to lower socio economic class, could be responsible for lower rate of selfmedication in our subjects.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9]13,15,17 Previous studies have shown that self-medication is more common with the educated and affluent. 7,12 The fact that our study population mainly belonged to lower socio economic class, could be responsible for lower rate of selfmedication in our subjects. Further, self-medication may be considered as an indirect indicator of quality of health care services and hence prevalence of self -medication is low in our region due to better access to health care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Easy availability of a wide range of medicines without prescription in India is a major factor responsible for irrational use of drugs resulting in health problems such as antimicrobial resistance, adverse drug events and economic loss. 9 This study attempted to find the prevalence of selfmedication with both, OTC and prescription only medicines (POM) among adults in urban Udupi taluk and to gain insight into associated factors.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Moreover in India, due to easy availability of drugs coupled with inadequate health services, increased proportions of drugs are used as self medication (for common complains and infective conditions), as compared to the prescribed drugs. [2] Hence, these consumers always face the threat of adverse drug reactions and drug interactions between active hidden ingredients of both herbal and allopathic drugs. Pharmacoepidemiological studies can help in minimizing the inherent risk of drug use in pregnancy, by establishing a profile of drug consumption, by evaluating the existing health services and by investigating the interventional measures.…”
mentioning
confidence: 99%